Isotonic regression analysis of Guzerá cattle growth curves - Rodrigues, Adriano; Monteiro Chaves, Lucas; Fonseca Silva, Fabyano; Pereira Garcia, Idalmo; Souza Duarte, Darlene Ana; Torres Ventura, Henrique (Revista Ceres, 2025)
The objective of this study was to apply data transformation via isotonic regression in growth curves studies of Guzerá cattle whose data presented disturbances characterized by decreased body weight in certain age groups. Weightage data were collected on newly weaned Guzerá males according to the methodology of weight gain tests (WGT) defined by the Brazilian Association of Zebu Breeders (ABCZ). The Logistic, Von Bertalanffy and Gompertz models were fitted to weight-age data using the generalized least squares method for non-linear regression models through the Gauss-Newton algorithm. The proposed transformation based on isotonic regression theory proved to be efficient; and the Logistic model was the best to describe the growth of animals, with a high percentage of convergence (100%) and goodness of fit assessed by the mean squared error (MSE) and the coefficient of determination (R2).